Correction: A dual stimuli responsive fluorescent probe carrier from a double hydrophilic block copolymer capped with β-cyclodextrin. Issue 30 (13th July 2016) - Yang, Guang; Yang, Zhen; Mu, Chengguang; Fan, Xiaodong; Tian, Wei; Abidian, Mohammad Reza; Wang, Qing
Abstract : Correction for 'A dual stimuli responsive fluorescent probe carrier from a double hydrophilic block copolymer capped with β-cyclodextrin' by Guang Yang et al., Polym. Chem., 2015, 6, 3382–3386.